„Uporządkujcie we mnie miłość” (Pnp 2, 4, LXX) w egzegezie wybranych autorów wschodu i zachodu - Nocoń, Arkadiusz (Vox Patrum, 2018)
“You set charity in order in me” (Song 2:4, LXX) is one of the most fundamental biblical texts for the concept of the ordo caritatis. The Author seeks to examine how this text was read in the East and West, analysing the commentary of three Greek authors (Origen, Gregory of Nyssa and Theodoret of Cyrus), and three Latin authors (Augustine of Hippo, John Cassian and Apponius). There commentaries, he notes, agree with one another for the most part, and refer more or less to Origen’s exegesis of this verse. However, some differences can be noted. The Eastern Fathers, for example, hold that, in the order of charity, the criterion of merit is more important than the criterion of blood relationship; that is to say, the greater love is to be shown to those who have been born in Christ (cf. 1Cor 4:15) over those born of the flesh. Only the Eastern Fathers explore what the ordo caritatis means also in relation to one’s enemies. The Western Fathers, for their part, tend to underline the moral aspect of the ordo caritatis, insofar as upholding that order is virtue, while infringing it is sin. In this regard, a casuistic approach can occur in their commentary more frequently than in those of the Eastern Fathers. The novelty of the commentaries of the Western Fathers is also found in their reflection on the ordo caritatis within the Holy Trinity, as well as the manner in which they expand the embrace of this order to other categories of people: friends, fellow citizens, strangers. Some of the Western Fathers (Apponius) apply the ordo caritatis not only to people but also to works of mercy, while others (Augustine) bring out the aesthetic element in the ordo caritatis, noting that the effect of order of any kind, including the order of charity, is beauty.